A versatile Multisite Gateway‐compatible promoter and transgenic line collection for cell type‐specific functional genomics in Arabidopsis. (21st January 2016) - Marquès‐Bueno, Maria Mar; Morao, Ana K.; Cayrel, Anne; Platre, Matthieu P.; Barberon, Marie; Caillieux, Erwann; Colot, Vincent; Jaillais, Yvon; Roudier, François; Vert, Grégory
Summary: Multicellular organisms are composed of many cell types that acquire their specific fate through a precisely controlled pattern of gene expression in time and space dictated in part by cell type‐specific promoter activity. Understanding the contribution of highly specialized cell types in the development of a whole organism requires the ability to isolate or analyze different cell types separately. We have characterized and validated a large collection of root cell type‐specific promoters and have generated cell type‐specific marker lines. These benchmarked promoters can be readily used to evaluate cell type‐specific complementation of mutant phenotypes, or to knockdown gene expression using targeted expression of artificial miRNA. We also generated vectors and characterized transgenic lines for cell type‐specific induction of gene expression and cell type‐specific isolation of nuclei for RNA and chromatin profiling. Vectors and seeds from transgenic Arabidopsis plants will be freely available, and will promote rapid progress in cell type‐specific functional genomics. We demonstrate the power of this promoter set for analysis of complex biological processes by investigating the contribution of root cell types in the IRT1‐dependent root iron uptake. Our findings revealed the complex spatial expression pattern of IRT1 in both root epidermis and phloem companion cells and the requirement for IRT1 to be expressed in both cell types for proper iron homeostasis. Significance Statement: In multicellular organisms, different cell types often perform discrete functions. Here we present a collection of benchmarked cell type‐specific promoters for functional genomics in Arabidopsis root, and use this resource as a test case to spatially deconstruct iron uptake.